1994
DOI: 10.2172/10189536
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocyanide safety program: An assessment of the possibility of ferrocyanide sludge dryout

Abstract: This report wasprepared as an account of work sponsored by an agency of t h e United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, make any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

1994
1994
1995
1995

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…Nominal heat loads calculated by McLaren (1994aMcLaren ( , 1994b) compared very favorably with those calculated independently in 1993 (Crowe et al 1993). A dryout analysis was also completed and released in FY 1994 (Epstein et al 1994 241-BY-104 (McLaren 1993) suggested that if hot spots with temperatures of concern are possible, surface temperature differences might be great enough to be detected by IR mapping.…”
Section: Instrument Treesmentioning
confidence: 90%
See 4 more Smart Citations
“…Nominal heat loads calculated by McLaren (1994aMcLaren ( , 1994b) compared very favorably with those calculated independently in 1993 (Crowe et al 1993). A dryout analysis was also completed and released in FY 1994 (Epstein et al 1994 241-BY-104 (McLaren 1993) suggested that if hot spots with temperatures of concern are possible, surface temperature differences might be great enough to be detected by IR mapping.…”
Section: Instrument Treesmentioning
confidence: 90%
“…The new data that have warranted this action include the following: (1) many of the TC elements in the existing trees have been returned to service, and measured temperatures are as expected; (2) thermal modeling to date (McLaren 1994a(McLaren , 1994b and an enhanced understanding of waste properties show that formation of hot spots in ferrocyanide tanks is not credible (Dickinson et al 1993, Epstein et al 1994; and (3) new calculations of tank heat content based on tank temperatures show lower values than previous estimates (Crowe et al 1993, McLaren 1994a.…”
Section: Instrument Treesmentioning
confidence: 99%
See 3 more Smart Citations